2006
DOI: 10.1136/emj.2005.032359
|View full text |Cite
|
Sign up to set email alerts
|

Patients either contacting a general practice cooperative or accident and emergency department out of hours: a comparison

Abstract: Introduction: Lack of collaboration between general practice (GP) cooperatives and accident and emergency (A&E) departments and many self referrals may lead to inefficient out-of-hours care. Methods: We retrospectively analysed the records of all patients contacting the GP cooperative and all patients self referring to the A&E department out of hours in a region in the Netherlands. Results: 258 patients contacted the GP cooperative and 43 self referred to the A&E department per 1000 patients per year. A wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
71
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 13 publications
(17 reference statements)
18
71
4
1
Order By: Relevance
“…This mismatch between their expectations of the consultation and the actual outcome needs to be addressed, 29 again through awareness-raising, education, and training. There is evidence that this can be successfully achieved, 30 but the findings of this study suggest that some service users perceive individual advice that is contrary to such goals, and this must be addressed urgently.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 79%
“…This mismatch between their expectations of the consultation and the actual outcome needs to be addressed, 29 again through awareness-raising, education, and training. There is evidence that this can be successfully achieved, 30 but the findings of this study suggest that some service users perceive individual advice that is contrary to such goals, and this must be addressed urgently.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 79%
“…One study found that 50% of self-referrals attend for injuries and ask for X-rays that would usually not be provided by a general practice but will be provided by an A&E centre (Giesen et al 2006). Patients often indicate that recommendations by family or friends influenced their decision to visit the A&E (Giesen et al 2006;Penson et al 2011). Patients also appear to search online for healthcare information before attending A&E (Benger and Jones 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Users present with a wide range of conditions -some of which, although serious, may not warrant a specialist service. Complaints from staff about attendees 'that could have seen by their own GP instead' are therefore longstanding (Giesen et al, 2006;Murphy, 1998a;, 1998b;Sempere-Selva et al, 2001). Within London, Southwark and Lambeth Primary Care Trusts (PCTs) have each experienced a rise in the use of A&E and associated costs in recent years.…”
Section: Using Names To Classify Light Aande Usersmentioning
confidence: 99%